Two theater plays by Domingo Miral in "fabla chesa" - Enguita Utrilla, José María (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In 1902, and within the festivities of the Villa de Hecho (Huesca), the comedy Qui bien fá nunca lo pierde was performed in the vernacular of this town. Published the following year in Jaca, along with the sainete Tomando la fresca en la Cruz de Cristiano ó á casarse tocan, both works constitute the first written testimony of contemporary Cheso. And to its author, Don Domingo Miral, corresponds, therefore, the title of pioneer of Chesa literature, opening a path that many other writers from that beautiful Pyrenean corner have been expanding to this day. The following comments will deal with Don Domingo Miral, the linguistic and literary value of these theatrical pieces and their importance for the continuity of the Cheso as a sign of local identity.